Intussusception secondary to Vanek’s tumor - Merchán, Pablo; Petracchi, Enrique; Muthular, Magali; Rocco, Lucía; Canullán, Carlos (Cirugía del Uruguay, 2021)
Vanek's tumor also knows as inflammatory fibroid polyp is a benign tumor of submucosal origin, which can present as an infrequent case of intussusception in adults. It affects both sexes and is more frequent between the fifth and seventh decade of life. We present the case of a 42-year-old woman who consults for abdominal pain with a later diagnosis of intussusception due to tumor.